(untitled) (Mustansiria Dental Journal, 2022)
Aim: The aim of this research was to examine physical attributes of two calcium silicate-based liner" Mineral trioxide aggregate (MTA), and resin modified calcium silicate (Theracal LC)". Material and Methods: Ten discs of each tested material were prepared according to manufacturer instructions of each material, then pasted onto molds and allow to set then tested, porosity, water sorption and solubility were measured using mass measurements. Results: Theracal LC has lower water sorption, solubility, and porosity than MTA (p<0.05). Conclusion: Theracal LC has better physical properties than MTA.